Pacatus : Panegyric to the Emperor Theodosius - Pacatus Drepanius, Latinus, činný 4. století (Translated texts for historians. Latin series ;, 1987)
This series is designed to meet the needs of students of ancient and medieval history and others who wish to broaden their study by reading source material, but whose Latin and Greek is not sufficent to allow them to do so in the original language. Pactatus' panegyric celebrates Theodosius' victory over the usurper Magnus Maximus, whose rebellion in Britain, murder of Gratian, and occupation of Gaul rent the Western Empire and threw the court of Milan into turmoil in the 380s.